THE EFFECTIVENESS OF PEER GROUP COGNITIVE BEHAVIOR COUNSELING ON BODY IMAGE IMPROVEMENT IN FEMALE ADOLESCENT - Nirwan; Said Devi Elvin; Julianti Jauhari (Jurnal Ilmiah Keperawatan, 2024)
Greater attention to appearance, clothing, grooming, hairstyle, and behavior is a phenomenon that occurs among adolescents. Adolescents believe that self-appearance is very important for social acceptance, especially acceptance from peers. Furthermore, adolescents want to always look attractive to others, especially peers. This phenomenon can cause body image disorder and low self-esteem especially among female adolescents. It is believed that group counseling can improve the body image of female adolescent to be more positive. This research aims to determine the effect of counseling methods with a cognitive behavioral approach on improving body image in female adolescent. This study used a quasi-experimental design. The sample was identified by using power analysis, the number of sample in this study was 128 female adolescents which included two groups namely intervention group and control group, composed of 64 respondents in each group. The data was collected by using the Body Appreciation Scale (BAS) questonnaire to measure body image variable. The Cognitive Behavior Group Counseling approach was used to provide counseling to the intervention group for six sessions. Body image measurements were carried out three times, namely before counseling, a week after counseling, and two weeks after counseling. The data analysis was carried out using a two-mean difference test. The result showed that cognitive behavior group counseling was effective in improving the body image of female adolescent to be more positive (p value = 0,000 < 0,05). It is concluded that cognitive behavior group counseling is an effective intervention to help female adolescent in building a positive body image.